1997
DOI: 10.1523/jneurosci.17-11-04243.1997
|View full text |Cite
|
Sign up to set email alerts
|

Implication of OTX2 in Pigment Epithelium Determination and Neural Retina Differentiation

Abstract: The expression pattern of Otx2, a homeobox-containing gene, was analyzed from the beginning of eye morphogenesis until neural retina differentiation in chick embryos. Early on, Otx2 expression was diffuse throughout the optic vesicles but became restricted to their dorsal part when the vesicles contacted the surface ectoderm. As the optic cup forms, Otx2 was expressed only in the outer layer, which gives rise to the pigment epithelium. This early Otx2 expression pattern was complementary to that of PAX2, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 48 publications
6
123
0
Order By: Relevance
“…Our results confirm other studies done on chick (Bovolenta et al, 1997) that early in retina formation, XOtx2 transcripts are found in all layers of the neural retina. Yet, if XOtx2 is involved in bipolar cell specification in Xenopus, why do not all cells become bipolar cells?…”
Section: Photoreceptors Versus Bipolars Otx5b Versus Otx2supporting
confidence: 93%
See 2 more Smart Citations
“…Our results confirm other studies done on chick (Bovolenta et al, 1997) that early in retina formation, XOtx2 transcripts are found in all layers of the neural retina. Yet, if XOtx2 is involved in bipolar cell specification in Xenopus, why do not all cells become bipolar cells?…”
Section: Photoreceptors Versus Bipolars Otx5b Versus Otx2supporting
confidence: 93%
“…otd (also known as oc; ocelliless) is the only otd/Otx family member identified in Drosophila and it contributes to head formation (Finkelstein et al, 1990). The vertebrate homologues of otd include Otx1, Otx2,Otx3,Otx4,Otx5,Otx5b (96% similar to Otx5) and Crx, which are all involved in anterior embryo and sensory organ formation (Acampora et al, 1998a;Acampora et al, 1998b;Acampora et al, 1996;Acampora and Simeone, 1999;Andreazzoli et al, 1997;Bovolenta et al, 1997;Furukawa et al, 1997;Gammill and Sive, 1997;Kablar et al, 1996;Kuroda et al, 2000;MartinezMorales et al, 2001;Pannese et al, 1995;Sauka-Spengler et al, 2001;Suda et al, 1999;Vignali et al, 2000). The first vertebrate homologues of otd, Otx1 and Otx2, were characterised in mouse (Simeone et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the number of Otx2 + retinal progenitors (supplementary material Fig. S1G,I) (Bovolenta et al, 1997) and that of Tuj1 + or islet 1/2 (Isl1/2) + differentiating neurons (Esteve et al, 2011) was reduced in E12/E13 Meis1 −/− retinas (Fig. 2J,L,M,O).…”
Section: Microphthalmia Is Associated With Decreased Neurogenesis Andmentioning
confidence: 99%
“…OTX2 is a bicoid-type homeodomain transcription factor important in retinal differentiation and fore and midbrain development (Bovolenta et al, 1997;Simeone et al, 1993). Heterozygous loss of function mutations in OTX2 are a rare cause of the anophthlamia or severe microphthalmia phenotype occurring in approximately 2% of patients (Table 1).…”
Section: Otx2mentioning
confidence: 99%